2019
DOI: 10.3390/su11216048
|View full text |Cite
|
Sign up to set email alerts
|

Application of Building Performance Simulation to Design Energy-Efficient Homes: Case Study from Saudi Arabia

Abstract: The per capita energy usage in Saudi Arabia is almost three times higher than the global average. A major contributor is the residential sector which consumes almost 50% of the total national energy consumption every year. Environmental and economic pressures along with the Saudi Vision 2030 reform program advocate for an improvement in energy consumption patterns. For a sustainable residential sector, energy-efficient solutions should be adopted in the design process preferably based on building performance s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 29 publications
(22 citation statements)
references
References 27 publications
9
11
0
Order By: Relevance
“…The results of energy savings are represented in Figure 16 and show that the WWR has a very low effect on energy demand. These results are similar to the results found by (Ahmed et al, 2019) that also showed minimal effect when using a lower WWR. On the other hand, the results found by (Wahl, 2017) show that reducing the WWR and modifying the window allocation can save energy up to 19% for Riyadh.…”
Section: Energy Efficiency Measuressupporting
confidence: 91%
See 1 more Smart Citation
“…The results of energy savings are represented in Figure 16 and show that the WWR has a very low effect on energy demand. These results are similar to the results found by (Ahmed et al, 2019) that also showed minimal effect when using a lower WWR. On the other hand, the results found by (Wahl, 2017) show that reducing the WWR and modifying the window allocation can save energy up to 19% for Riyadh.…”
Section: Energy Efficiency Measuressupporting
confidence: 91%
“…The maximum reduction in energy consumption was 4.1% when an overhang projection of 100 cm were considered for Riyadh. Energy savings represented in Figure 17 are in range with that presented by (Alaidroos and Krarti, 2015) and (Ahmed et al, 2019), who showed that overhangs of 100 cm can save energy by 6% and 3%, respectively for Riyadh. However, these results were lower than the results found by (Wahl, 2017), which showed a combination of shades and fines on all fac¸ades excluding the south causes energy savings of 8.4% for Riyadh.…”
Section: Energy Efficiency Measuressupporting
confidence: 75%
“…There are also many studies for electrical energy consumption in the domestic sector in the KSA in literature. Ahmed et al [20] performed a simulation study and showed that the annual energy used intensity (EUI) of a villa could be decreased from 148.8 to 72.5 kWh/m 2 , which is 51.3% of the existing typical residential villa. The buildings profoundly depend on A/C, which uses about 80% of domestic electricity only envelope insulation.…”
Section: Literature Reviewmentioning
confidence: 99%
“…In addition, KSA was the largest utilizer of fossil fuels among the Gulf Cooperative Council (GCC) countries and ranked 15th among global countries in 2008 [7,8]. The buildings and construction sector accounts for majority of the energy consumption in the country, and the abnormally high consumption in the sector is as a result of the desert climate of the country, outdated construction sector, subsidized utilities, rapid growth, lack of awareness about sustainability, and absence of codes/guidelines [9][10][11].…”
Section: Introductionmentioning
confidence: 99%